KREDIBILITAS CELEBRITY ENDORSER DAN MINAT BELI PENGGEMAR RAFFI AHMAD DAN NAGITA SLAVINA TERHADAP SKINCARE MS GLOW - Siti Barokah; Dinar Mustofa; Putri Patricia Rahmadani (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The competition in the cosmetic industry business is getting tougher and more challenging for the perpetrators. To face this competition in order to continue to exist in the cosmetic market, business actors are actively hooking up customers by partnering with a number of celebrities. Business people are competing to like their cosmetic products by applying celebrity endorser services. This research was conducted with the aim of finding out how credible celebrity endorsers Raffi Ahmad and Nagita Slavina are in promoting ms glow products and any effects on the buying interest of celebrity fans of the celebrity couple Raffi Ahmad and Nagita Slavina. The research method used in this research is descriptive qualitative. The data techniques used were observation, interview and documentation. The results of this study indicate that Raffi Ahmad and Nagita Slavina have high credibility in endorsing ms glow products and are able to foster buying interest among fans of ms glow products as the products they promote.